2013
DOI: 10.1155/2013/383698
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Scaling for Orthodontic Root Resorption

Abstract: The paper investigates the risk factors for the severity of orthodontic root resorption. The multidimensional scaling (MDS) visualization method is used to investigate the experimental data from patients who received orthodontic treatment at the Department of Orthodontics and Dentofacial Orthopedics, Faculty of Dentistry, “Carol Davila” University of Medicine and Pharmacy, during a period of 4 years. The clusters emerging in the MDS plots reveal features and properties not easily captured by classical statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Root shortening was detected in 62% of the upper central incisors, 53% of upper lateral incisors, 48% of upper second premolars, 48% of lower lateral incisors, 50% of lower canine, and 51% of lower second premolars, with a formula previously proposed [19].…”
Section: Age Distributionmentioning
confidence: 70%
See 2 more Smart Citations
“…Root shortening was detected in 62% of the upper central incisors, 53% of upper lateral incisors, 48% of upper second premolars, 48% of lower lateral incisors, 50% of lower canine, and 51% of lower second premolars, with a formula previously proposed [19].…”
Section: Age Distributionmentioning
confidence: 70%
“…The reported frequency of external root resorption is about 100% when it is examined under microscopy. When it is quantified on periapical or panoramic radiographs, the frequency falls to 70%, with a mean reported value of root shortening of 1.42 ± 0.44 mm and 1% to 5% of the cases with a loss of 4mm or one-third of root length [19]. In addition, maxillary teeth are more sensitive than mandibular teeth to root resorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that orthodontic treatment causes mechanical trauma to the periodontal ligament and induces pulpal reactions . The most frequently reported side effect is external root resorption, a process characterized by the destruction of root structure , with the subsequent diminution of root length (mean reported value of 1.42 ± 0.44 mm) . Another side effect is the reduction in pulp chamber dimensions, owing to secondary dentine formation .…”
Section: Discussionmentioning
confidence: 99%
“…MDS tools have been widely used in finance, social sciences, biology, and other disciplines (Preoteasa et al 2013), but studies in seismology remain scarce. Previous works may be found in Dzwinel et al (2005).…”
Section: Introductionmentioning
confidence: 99%